Comparative Study of Snodgrass and Mathieu's Procedure for Primary Hypospadias Repair. (27th April 2014) - Hamid, Raashid; Baba, Aejaz A.; Shera, Altaf H.
Abstract : Objective . Present study was undertaken to compare the results of two single stage hypospadias repairs, namely, Tubularized Incised Plate (TIP) repair and Mathieu's repair. Methods . The study included 100 patients of distal penile hypospadias, from January, 2008 to January, 2013. After a detailed history, local examination was performed with reference to the site of meatus, shape of glans, and presence of chordee. TIP repair was performed in 52 patients and Mathieu's repair in 48 patients. On follow-up, the patients were examined for the position of meatus, shape of meatus, urinary stream, urethrocutaneous fistula, and stricture formation. Results . The mean age of presentation was 6.2 ± 3.2 years (range 1.5–15years). The mean operative time was 63.7 ± 14.3 (45–90) minutes and 95.0 ± 19.1 (70–125) minutes in TIP and Mathieu's repair, respectively.Complications after surgery were urethero cutaneous fistula in 3(5.76%) and 7 (14.5%), meatal stenosis in 3(5.33%) and 4(8.33%), wound infection in 19.2% and 8.3% cases in TIP repair and Mathieu repair, respectively. The shape of meatus was slit-like and vertically oriented in 48(92.3%) patients who had undergone TIP repair. Conclusion . The Snodgrass repair is significantly faster, with more natural cosmetic appearance of the meatus than the Mathieu's repair.